Association between tea consumption and prevention of coronary artery disease: A systematic review and dose-response meta-analysis - Yang, Xin; Dai, Haiyun; Deng, Ruihang; Zhang, Ziang; Quan, Yiwen; Giri, Mohan; Shen, Jian (Frontiers in Nutrition, 2022)
Background: Evidence from previous studies reporting on the relationship between tea consumption and its preventive effect on coronary artery disease (CAD) has conflicting outcomes. With the accumulation of new clinical evidence, we conducted this meta-analysis to assess tea consumption and CAD risk. Methods: We searched PubMed, EMBASE, Cochrane Library, and Medline databases for published observational studies from their inception to May 2022. A random-effects model was used to calculate risk ratios with 95% confidence intervals. We also conducted linear and nonlinear dose-response meta-analyses to analyze the association. We regarded that one cup equals 237 mL. Subgroup analyses and univariate meta-regression were conducted to explore the source of heterogeneity. Results: A total of 35 studies, including 24 on green tea and 11 on black tea consumption, were included in this meta-analysis. An inverse association for the risk of CAD was observed for black tea (RR: 0.85; 95% CI: 0.76, 0.96) and green tea (RR: 0.93; 95% CI: 0.88, 0.99). The dose-response meta-analysis showed that drinking less than four cups of black tea daily may effectively prevent CAD, while more than 4-6 cups/d will promote disease risk. Furthermore, the dose-response relationship between green tea consumption and the prevention of CAD showed that the risk of CAD gradually decreased as green tea consumption increased. We also demonstrated that the more cups of green tea consumed, the lower the risk of CAD. In the subgroup analysis by continent, a significant negative correlation between CAD risk and green tea consumption was observed in the Asian population (RR: 0.92; 95% CI: 0.85, 0.99) but not in the western population [North America (RR: 0.97; 95% CI: 0.92, 1.03), Europe/Oceana ( RR: 0.91; 95% CI: 0.78, 1.07)]. Conclusions: Higher green tea consumption was associated with reduced CAD risk. However, drinking more than 4-6 cups of black tea daily may raise the CAD risk. This study offers new insight into the relationship between tea consumption and its preventive effect on CAD. However, further large prospective cohort studies are needed to validate these findings.